Polynomial extensions of Krull modules - Akalan, E.; Marubayashi, H. (Communications in algebra, 2023)
Let M be a torsion-free module over an integral domain D with quotient field K. In this paper, we show that M is a Krull module over D in the sense of Costa-Johnson (Inert extensions of Krull domains, 1976) if and only if the polynomial module is a Krull module over in the sense of Costa-Johnson.